DEVELOPMENT AND VALIDATION OF INSTRUCTIONAL MATERIALS IN MUSIC - ALONZO, ELIZABETH HIPOLITO (International Journal of Psychosocial Rehabilitation, 2020)
–Songs serve as a unifying factor to a group of people and this could be a great help for them to express their sentiments and emotions. In a certain community songs are part and parcel of every culture. It conveys the people’s identity and reflects how richness of such culture.Specifically, it aimed to find out the elements of music and musical notations that are dominantly seen in the Ibanag songs in terms of rhythm, time signature and key signature. It also explored the values and dominant themes as reflected and found in the Ibanag folk songs. It also dwelled on the surfacing identity, personality, and worldviews of the Ibanags as reflected on the songs. The development of instructional materials and proposed for music in the educational institutions would help improve and enrich curriculum particularly in contextualization and indigenization of basic education curriculum.The study employed a qualitative type of research, the elements of music and musical notations were dominantly seen in the Ibanag songs in terms of: rhythm, time signature and key signature was analyzed using Fairclough’s model on Critical discourse analysis to include among others values that are reflected in the Ibanag folk songs, dominant themes are found in the Ibanag folk surfacing identity and personality of the Ibanags that be deduced from these songs and its worldviews. In the process of transcription, this was transcribed in English and was also subjected for validation by experts.